Frequency reconfigurable archimedean spiral antenna - Abdul Rahman, Masmurni (2012)
The latest evolution of communication technology system has observed an emerging of new multi-functional devices and new applications operating in different frequencies. As the technology advances, it becomes apparent that a transceiver which could operate at multi-frequency is in need to support the system. Hence in this thesis, a frequency reconfigurable switchable between wideband and narrowband has been proposed and investigated. The idea was to support a wide frequency of operation and at the same time could be switched to operate at a single frequency in order to reduce the interference level at the receiver. This antenna is potentially useful for UWB and future cognitive radio systems. The proposed antenna utilized an Archimedean spiral antenna as the wideband antenna, and it was reconfigured by adding a slot resonator to the structure to enable narrowband operation. Two ideal switches in the form of metal pads are used for the studies to enable the reconfiguration capability. Performance results from the measurements and simulations results shows a good agreement in terms of return loss and radiation pattern which shows a broad bandwidth operation at wideband operation and 16% bandwidth for the narrowband operation with a maximum gain of 3dBi at the frequency of operation.